MODEL MANAJEMEN SDM DALAM IMPLEMENTASI ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) DI PERUSAHAAN INDONESIA - Johan Maulana; Kamsidik Kamsidik (Yayasan Education and Social Center, 2026)
The implementation of Environmental, Social, and Governance (ESG) principles has become a strategic imperative for companies in Indonesia in response to regulatory pressures, stakeholder demands, and the need for long-term sustainability. However, ESG implementation has not yet been systematically integrated into Human Resource Management (HRM) practices. This study aims to analyze and formulate an effective HRM model to support ESG implementation in Indonesian companies. The research employs a qualitative approach using a literature review and case study design involving several companies that have adopted ESG principles. Data were collected through document analysis, sustainability reports, and in-depth interviews with HR practitioners and sustainability managers. The findings indicate that ESG implementation through HRM can be optimized by integrating sustainable recruitment policies, developing green competencies, applying sustainability-based performance appraisal systems, fostering an ethical and inclusive work culture, and strengthening transparent and accountable HR governance. The proposed ESG-based HRM model is able to enhance organizational performance, corporate reputation, and employee commitment to sustainability. This study contributes theoretically to the development of a sustainable HRM model and provides practical implications for companies and policymakers in strengthening ESG implementation in Indonesia. The implementation of Environmental, Social, and Governance (ESG) principles has become a strategic imperative for companies in Indonesia in response to regulatory pressures, stakeholder demands, and the need for long-term sustainability. However, ESG implementation has not yet been systematically integrated into Human Resource Management (HRM) practices. This study aims to analyze and formulate an effective HRM model to support ESG implementation in Indonesian companies. The research employs a qualitative approach using a literature review and case study design involving several companies that have adopted ESG principles. Data were collected through document analysis, sustainability reports, and in-depth interviews with HR practitioners and sustainability managers. The findings indicate that ESG implementation through HRM can be optimized by integrating sustainable recruitment policies, developing green competencies, applying sustainability-based performance appraisal systems, fostering an ethical and inclusive work culture, and strengthening transparent and accountable HR governance. The proposed ESG-based HRM model is able to enhance organizational performance, corporate reputation, and employee commitment to sustainability. This study contributes theoretically to the development of a sustainable HRM model and provides practical implications for companies and policymakers in strengthening ESG implementation in Indonesia.